Urine Screening for Opiod and Illicit Drugs in the Total Joint Arthroplasty Population - Vopat, Matthew; Messamore, William; Trent, Jesse; Schmanke, Ken; Zackula, Rosey; Yang, Shang-You; Bhargava, Tarun (Kansas Journal of Medicine, 2020)
Introduction. Recent studies have shown an increase in post-operative orthopaedic complications associated with pre-operative opioid use. It is, therefore, important to know if patients use opioids before scheduled surgery. The purpose of this study was to determine if urine drug screening (UDS) is an effective screening tool for detecting opioid and illicit drug use prior to joint arthroplasty (JA) procedures.Methods. This retrospective chart review was performed with IRB approval on 166 out of 172 consecutive patients in a community-based practice. All the patients had a pre-operative UDS prior to primary or revision JA by a fellowship trained orthopaedic surgeon between March 2016 and April 2017. Patient demographics documented opioid and illicit drug use, co-morbid diagnosis, and UDS results were collected from clinical charts. Statistical analysis was conducted using Pearson Chi-square, Fisher’s exact, McNemar test, and t-tests with IBM SPSS Statistics, ver. 23. Significant differences were p < 0.05.Results. Sixty-four of 166 patients (38.6%) tested positive for opioids. Among them, 55.0% (35/64) had no history of prescription opioid use. Significant differences were observed when comparing the test results of the UDS with the patient reported history of prescribed opioids (p = 0.001).Conclusion. With a significant number of patients testing positive for opioids without evidence of a previous prescription, UDS may be beneficial for initial risk assessment for patients undergoing JA procedures.